Geometry For Dummies. - Ryan, Mark (Wiley, 2016)
Students studying geometry in school will certainly learn about lines and angles, circles and triangles, and they'll find everything they need to master those topics. But Geometry is so much more than shapes! Proofs are at the heart of any Geometry course, and they're most often where students struggle. Geometry For Dummies, 3rd Edition, is overflowing with helpful and practical, plain-English information about proofs to help students succeed. --Publisher's description.